Skabies : Patogenesis, Transmisi, Diagnosis, dan Terapi - Sri Agustina; Erni Setiyawati; Moh. Fatha Hernanda (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Scabies is a skin disease with itchy symptoms, especially at night, caused by Sarcoptes scabiei. This disease is a public health problem that mostly attacks children and the elderly. This disease has a significant impact on children's long- term health because it is often ignored and does not receive appropriate treatment. This paper will discuss everything about scabies cases from pathogenesis, transmission, diagnosis and therapy.